Preparing for the Application of A.I. in Business Operations - Kasem, Saisunee; Tengtrairat, Naruephorn; Wiriyametee, Benjakanlaya (RMUTL Journal of Business Administration and Liberal Arts, 2025)
The shift in technology trends has undeniably become a significant factor in the global and Thai digital economies. Artificial intelligence (A.I.) is an innovation that has taken a prominent role in the business world. The use of innovation in business is a key to developing the country's economic system and the survival of businesses. A.I. has become an essential tool for enhancing the ability and efficiency of doing business. The application of A.I. can help organizations work more efficiently, reduce costs, increase the speed of decision-making, and create a better experience for customers. However, the adoption of A.I. in the business sector still presents several challenges. Therefore, this article aims to present the importance of A.I., its applications in business, trends in Thailand, preparing businesses to use A.I. effectively, the benefits of using A.I. technology in business, and the risks and limitations of A.I., such as technological constraints, development costs, and ethical and data privacy issues. In the context of Thailand, the trend of adopting A.I. is still in its early stages, requiring the development of infrastructure, laws, and highly skilled workers. Careful study and planning before implementation will ensure that the application of A.I. is smooth and achieves sustainable success.